Analysis of causes for chronic gastric and duodenal ulcer disease prevalence among patients hispitalized in Regional Hospital in Zamość - Wójtowicz-Chomicz, Katarzyna; Kowal, Małgorzata; Liga-Car, Aneta; Borzęcki, Andrzej (Polish Journal of Public Health, 2009)
Introduction. Due to the high contribution of environmental factors, ulcer disease is reported as social and civilization disease. It is one of the most frequently occurring ailments of alimentary tract. According to general opinion, ulcer disease is multifactorial. H.pylori, stress, irregular diet, alcohol abuse and non-steroidal anti-infl ammatory drugs have crucial role in disease development.Aim of the work. Analysis of factors causing ulcer disease incidences among patients hospitalized in Regional Hospital in Zamość was the objective of the work.Materials and methods. Medical history of patients as well as analysis of their disease background were considered. Studies were carried out from January – December, 2006 among 246 people.Results:1. Significant percentage of ulcer disease refers to H.pylori infection as well as to the use of non-steroidal antiinflammatory drugs.2. In most of the cases there are several risk factors of ulcer disease.3. Bleeding from superior portion of alimentary canal was the most frequently occurring complication.